Pengaruh Model Pembelajaran Problem Based Instruction Berbasis Collaboration, Communication, Creativity and Critical Thinking Terhadap Hasil Belajar Rangkaian Elektonika - Ayu Alam Pertiwi; Fahmi Rizal (invotek, 2020)
4C (Collaboration, Communication, Creativity and Critical Thinking) skill-based Problem Based Instruction (PBI) is student-centered learning so that it can do problem solving activities and make students think more critically, present creative ideas and communicate with the lesson more broadly. The learning model is a planning guide in determining the set of lessons in the classroom. Learning on students is still centered on the teacher or conventional so it does not provide opportunities for students to express ideas as if students think in communication, collaboration, creative and critical thinking. This study aims to determine the effect of the 4C Skill-based Problem Based Instruction learning model on electronic learning outcomes. The 4C skill-based PBI learning model uses a quasy type of experimental research. In this study the effect of the treatment (treatment) was analyzed by different tests, namely the group received different treatment, namely the experimental group PBI learning based on 4C skills and the control group with conventional learning (two groups). From the results of the study showed an increase in the average value of learning outcomes of the experimental class was higher than the increase in the average value of the control class. It can be concluded that the learning outcomes of students who use the 4C-based problem based instruction learning model are better than students who use conventional learning.